Socioeconomic inequalities and changes in oral health behaviors among Brazilian adolescents from 2009 to 2012 - Freire, Maria do Carmo Matias; Jordão, Lidia Moraes Ribeiro; Malta, Deborah Carvalho; Andrade, Silvânia Suely Caribé de Araújo; Peres, Marco Aurelio (Revista de Saúde Pública, 2015)
OBJECTIVE To analyze oral health behaviors changes over time in Brazilian adolescents concerning maternal educational inequalities.METHODS Data from the Pesquisa Nacional de Saúde do Escolar(Brazilian National School Health Survey) were analyzed. The sample was composed of 60,973 and 61,145 students from 26 Brazilian state capitals and the Federal District in 2009 and 2012, respectively. The analyzed factors were oral health behaviors (toothbrushing frequency, sweets consumption, soft drink consumption, and cigarette experimentation) and sociodemographics (age, sex, race, type of school and maternal schooling). Oral health behaviors and sociodemographic factors in the two years were compared (Rao-Scott test) and relative and absolute measures of socioeconomic inequalities in health were estimated (slope index of inequality and relative concentration index), using maternal education as a socioeconomic indicator, expressed in number of years of study (>; 11; 9-11; ≤ 8).RESULTS Results from 2012, when compared with those from 2009, for all maternal education categories, showed that the proportion of people with low toothbrushing frequency increased, and that consumption of sweets and soft drinks and cigarette experimentation decreased. In private schools, positive slope index of inequality and relative concentration index indicated higher soft drink consumption in 2012 and higher cigarette experimentation in both years among students who reported greater maternal schooling, with no significant change in inequalities. In public schools, negative slope index of inequality and relative concentration index indicated higher soft drink consumption among students who reported lower maternal schooling in both years, with no significant change overtime. The positive relative concentration index indicated inequality in 2009 for cigarette experimentation, with a higher prevalence among students who reported greater maternal schooling. There were no inequalities for toothbrushing frequency or sweets consumption.CONCLUSIONS There were changes in the prevalences of oral health behaviors during the analyzed period; however, these changes were not related to maternal education inequalities.